Tâhâ Husayn et Le livre des jours ; Démarche autobiographique et structure narrative - Luc-Willy Deheuvels (Revue des Mondes Musulmans et de la Méditerranée)
Tâhâ Husayn's book, al-Ayyâm, is composed of three volumes. The first was written in 1926 and the third in 1955. As the author himself developed, so did his horizon. The Tâhâ Husayn of the 1920s was a polemicist who, in 1926, found himself in the midst of a grave crisis which concerned his book on the Jahiliyya poe-try : it was while in exile in France because of this crisis that he wrote the first part of al-Ayyâm. The choice of an autobiographical narration with literary aspirations was something new in Arab literature. The présent analysis which deals specifically with the first volume of al-Ayyâm stresses the individual quest for a memory tracing the steps of a movement towards reason which draws on memory to justify itself before the world. This personal itinerary is also a succession of stages which Tâhâ Husayn proposes to society in order for it to become reborn and for it to pass from an imaginary mythical point frozen over its own memory to the maturity of a scien-tific and rational outlook.